Volvariella volvacea (Bull.) Singer mushroom production cultivated using oil palm empty fruit bunch in Ayer Hitam Forest Reserve, Puchong, Selangor, Malaysia - Eddy Warman, Nurul Kamaliah (2022)
Forest farming of straw mushrooms (Volvariella volvacea) could be a potential agroforestry practice that increases crop diversity while conserving forest ecosystem, however, there were some constraints on mushroom cultivation process. To date, specific information for straw mushroom cultivation using oil palm empty fruit bunch as substrate, particularly suitable microclimatic conditions, best practices, composting period and composting parameters are limited. Hence, the objectives of this study were; (i) to determine the effect of microclimate (air temperature, relative humidity, light intensity), and bed pH on V. volvacea mushroom production, (ii) to determine the effect of bed orientations, bed conditions (temperature, humidity, pH) and other attributes (i.e., harvesting week, cultivation month and replication) on V. volvacea mushroom production, and (iii) to assess the composting period and composting condition of EFB (temperature, pH, moisture content, oxygen level, and carbon monoxide level) on V. volvacea mushroom production in lowland dipterocarp forest. Outdoor cultivation method was carried out with four replications from November 2017 until May 2019. The microclimatic conditions (air temperature, relative humidity, light intensity) and bed pH were compared between replications. Generalized linear models (GLMMs) were used to examine the relationship of mushroom production with 7 predictor variables (bed temperature, bed humidity, bed pH, bed orientation, harvesting week, cultivation month and replication). Correlation tests for multi-collinearity among variables were also conducted. One-way ANOVA was done to determine the significant result between composting periods of 9 and 12 days on V. volvacea production. Additionally, the change in chemical composition of EFB was analyzed using FT-IR Spectroscopic Analysis. The results revealed that V. volvacea production was affected by microclimatic and bed conditions. The highest production of V. volvacea was recorded with 49,446 g that requires temperature, relative humidity, light intensity and bed pH at 29.4°C, 79.68%, 505.5 lx and pH 6.92, respectively. Bed orientations and bed pH were insignificant, however bed humidity, bed temperature, harvesting week, cultivation month and replication significantly influenced V. volvacea production. Composting periods of 9 and 12 days did not significantly affect the V. volvacea production. The highest production, R2 indicated that the suitable composting parameters were 33.65 - 71.47°C, pH 6.5 - 7, normal MC, oxygen level more than 10% and 0 - 90 rpm carbon monoxide. In conclusion, cultivation of V. volvacea is ethnically feasible under a tropical agroforestry system.